Jonathan Allen, ed., Lost Envoy: The Tarot Deck of Austin Osman Spare (London: Strange Attractor Press, 2016), 336 pp, £35 (cloth). (31st December 2017) - Cusack, Carole
Abstract : Jonathan Allen, ed., Lost Envoy: The Tarot Deck of Austin Osman Spare (London: Strange Attractor Press, 2016), 336 pp, £35 (cloth).